1995
DOI: 10.1021/j100013a053
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Solidification of Benzophenone in the Supercooled Liquid State

Abstract: A study of the solidification of supercooled liquid benzophenone (BZP) is presented. As is well-known, liquid BZP can be extensively supercooled without crystallization or glass formation. In the experiments, the BZP liquid -solid phase transition is activated by either seeding or momentary freezing (using liquid nitrogen) of a portion of liquid. Measurements of the position of the liquidsolid interface as a function of time are reported. In the case of seeding, the temperature dependence of the interface prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…At lower temperatures the metastable phase was found not to nucleate so easily, whilst below 203 K it has been suggested that a glassy phase, -benzophenone, exists. Recently, Graham et al (1995), who broadly con®rmed the results of the previous studies, investigated the formation of these different polymorphic modi®cations and developed a model of the solidi®cation process.…”
Section: Historical Backgroundmentioning
confidence: 96%
“…At lower temperatures the metastable phase was found not to nucleate so easily, whilst below 203 K it has been suggested that a glassy phase, -benzophenone, exists. Recently, Graham et al (1995), who broadly con®rmed the results of the previous studies, investigated the formation of these different polymorphic modi®cations and developed a model of the solidi®cation process.…”
Section: Historical Backgroundmentioning
confidence: 96%
“…in the Supporting Information). The recommended values of sublimation enthalpies at 298 15. K are Δ α g H m (298.15 K) = (94.96 ± 0.13) kJ•mol −1 and Δ β g H m Figure 6.…”
mentioning
confidence: 99%
“…However, with granular shocks above jamming the front propagates through an already-jammed medium and its speed is governed by elastic energy stored in particles [32,33]. Although supercooled liquids, like the system here, are initially unjammed, their solidification fronts propagate at a constant, thermodynamically favored speed [37]. The data in Fig.…”
Section: Boundary Effectsmentioning
confidence: 81%
“…These behaviors are reminiscent of shocks in granular systems above jamming [32,33] or solidification fronts in supercooled glass-forming liquids [34][35][36][37]. However, with granular shocks above jamming the front propagates through an already-jammed medium and its speed is governed by elastic energy stored in particles [32,33].…”
Section: Boundary Effectsmentioning
confidence: 99%